Pythagorean identity for polyharmonic polynomials - Allan Fryant; Murali Krishna Vemuri (International Journal of Mathematics and Mathematical Sciences)
Polyharmonic polynomials in n variables are shown to satisfy a Pythagorean identity on the unit hypersphere. Application is made to establish the convergence of series of polyharmonic polynomials.